2012
DOI: 10.1038/mt.2011.312
|View full text |Cite
|
Sign up to set email alerts
|

Nonmyeloablative Conditioning Regimen to Increase Engraftment of Gene-modified Hematopoietic Stem Cells in Young Rhesus Monkeys

Abstract: Immune responses to transgene products may lead to rejection of transduced cells, limiting successful gene therapy for genetic diseases. While moderate dosages of chemotherapeutic agents such as busulfan may increase hematopoietic stem cells (HSC) engraftment, they are not immune suppressive and do not abrogate immune responses to transgene products. Studies focused on nonmyeloablative conditioning with busulfan ± fludarabine in a clinically relevant monkey model to induce immune suppression to allow cells exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…These studies support that the route and timing of vector administration are crucial for limited biodistribution to other anatomical sites Conducted extensive analysis of gonads after various routes of lentiviral vector administration prenatally and confirmed no evidence of germ cell gene transfer in males or with organ-targeted approaches Tarantal et al, 2005). These studies further support the importance of organ-targeting and vector design (Pacak et al, 2006) to limit biodistribution Used SIV-based lentiviral vectors (Kahl et al, 2008) to transduce young monkey CD34 + hematopoietic stem/ progenitor cells for autologous transplantation, and used nonmyeloablative conditioning regimens such as busulfan and fludarabine (Kahl et al, 2006;Tarantal et al, 2012a) Addressed the role of overexpression of transforming growth factor-b 1 during fetal lung development, using an intrapulmonary gene transfer approach , providing a new model to explore lung disease that may allow greater insight into human lung development Reported that AAV8-mediated hepatic gene transfer in infant monkeys is safe and efficient but less stable when compared with adolescent animals Wang et al, 2011) Showed that in utero delivery of an AAV2/5-human FVII vector in the late third trimester confers therapeutic expression of human FVII at birth, which was maintained above baseline levels for at least 2 months, and that readministration with capsid proteins of another serotype (AAV2/8) *1 year after fetal gene delivery resulted in a further increase in plasma levels (Binny et al, 2012) Evaluated stem and progenitor cell age-related differences (fetal through aged) and showed significant differences across the lifespan (e.g., endothelial, hematopoietic, mesenchymal) (Lee et al, 2004Hacia et al, 2008;Kim et al, 2008;Shelley et al, 2012) Developed in vivo imaging techniques (PET, BLI) (Tarantal et al, , 2009(Tarantal et al, , 2012cTarantal and Lee, 2010) that demonstrated long-term gene expression, and showed engrafted foci of human cells at sites not appreciated by the collection of blood or bone marrow Showed high levels of firefly luciferase expression with no adverse effects up through *8 years postnatal age when organ-targeted fetal gene transfer approaches were used (e.g., intrathoracic, intrapulmonary, intramyocardial, intraportal, intrahepatic; lentiviral vectors or AAV serotypes) (Fig. 2).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…These studies support that the route and timing of vector administration are crucial for limited biodistribution to other anatomical sites Conducted extensive analysis of gonads after various routes of lentiviral vector administration prenatally and confirmed no evidence of germ cell gene transfer in males or with organ-targeted approaches Tarantal et al, 2005). These studies further support the importance of organ-targeting and vector design (Pacak et al, 2006) to limit biodistribution Used SIV-based lentiviral vectors (Kahl et al, 2008) to transduce young monkey CD34 + hematopoietic stem/ progenitor cells for autologous transplantation, and used nonmyeloablative conditioning regimens such as busulfan and fludarabine (Kahl et al, 2006;Tarantal et al, 2012a) Addressed the role of overexpression of transforming growth factor-b 1 during fetal lung development, using an intrapulmonary gene transfer approach , providing a new model to explore lung disease that may allow greater insight into human lung development Reported that AAV8-mediated hepatic gene transfer in infant monkeys is safe and efficient but less stable when compared with adolescent animals Wang et al, 2011) Showed that in utero delivery of an AAV2/5-human FVII vector in the late third trimester confers therapeutic expression of human FVII at birth, which was maintained above baseline levels for at least 2 months, and that readministration with capsid proteins of another serotype (AAV2/8) *1 year after fetal gene delivery resulted in a further increase in plasma levels (Binny et al, 2012) Evaluated stem and progenitor cell age-related differences (fetal through aged) and showed significant differences across the lifespan (e.g., endothelial, hematopoietic, mesenchymal) (Lee et al, 2004Hacia et al, 2008;Kim et al, 2008;Shelley et al, 2012) Developed in vivo imaging techniques (PET, BLI) (Tarantal et al, , 2009(Tarantal et al, , 2012cTarantal and Lee, 2010) that demonstrated long-term gene expression, and showed engrafted foci of human cells at sites not appreciated by the collection of blood or bone marrow Showed high levels of firefly luciferase expression with no adverse effects up through *8 years postnatal age when organ-targeted fetal gene transfer approaches were used (e.g., intrathoracic, intrapulmonary, intramyocardial, intraportal, intrahepatic; lentiviral vectors or AAV serotypes) (Fig. 2).…”
Section: Resultsmentioning
confidence: 73%
“…Primers and probes for quantitative PCR (qPCR) to assess biodistribution (DNA and RNA) ( Jimenez et al, 2005a;Tarantal et al, 2005Tarantal et al, , 2012a. Because of genomic homology, primer and probe sets based on human sequences may also amplify rhesus monkey genes, and thus the Center has developed a catalog of multiple sets of primers and probes that can distinguish between the species to meet the needs of various investigators and projects.…”
mentioning
confidence: 99%
“…For ADA-SCID, these include the possibility that the progenitors transduced in bulk CD34 + populations might be more differentiated than for SCID-X1, and that the level of vector-encoded ADA expression might be insufficient to support the development of a T cell leukemic phenotype, which has been shown to be associated with increased ADA expression 26 . Another notable difference between these two gene therapy trials was the use of sub-ablative busulfan conditioning in ADA-SCID patients, which is known to increase the level of bone marrow engraftment 27 . It is therefore conceivable that increased bone marrow engraftment may lead to increased thymic seeding with a resultant reduction in oncogenic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the acceptance of AUC as a predictive biomarker of the patient’s response to busulfan-containing HCT regimens, identifying novel biomarkers is desirable because of the rapidly evolving trend of shorter IV busulfan courses (Tarantal et al 2012) and because relapse and non-relapse mortality continue to be problematic even with PK-guided IV busulfan dosing (Jenke et al 2005; Rezvani et al 2013). McCune et al recently developed a population pharmacokinetic model for IV busulfan from a large cohort of HCT recipients (N=1610, 92% pediatric) (McCune et al 2014).…”
Section: Introductionmentioning
confidence: 99%